Languages in the Lutheran Reformation: Textual networks and the spread of ideas. Edited by Mikko Kauko, Miika Norro, Kirsi-Maria Nummila, Tanja Toropainen and Tuomo Fonsén. (Crossing Boundaries.) Pp. 307 incl. 10 figs and 1 table. Amsterdam, Amsterdam University Press, 2019. £90. 978 94 6298 155 3 - Berntson, Martin (The journal of ecclesiastical history, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0022046920001104/resource/name/firstPage-S0022046920001104a.jpg